2005
DOI: 10.1523/jneurosci.3866-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Activation during the Acquisition of a Multifrequency Bimanual Coordination Task: From the Cognitive Stage to Advanced Levels of Automaticity

Abstract: Little is known about activation changes reflecting overlearning, i.e., extensive motor training beyond asymptotic performance. Here we used functional magnetic resonance imaging to trace the neural shifts from an initial to a skilled (learning) and finally overlearned stage (automatization). Scanning occurred before training (PRE) and after 1 (MID) and 2 weeks (POST) of intensive practice on a new bimanual coordination task (Ͼ10,500 cycles). Kinematics revealed major improvements between PRE and MID sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
3
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(157 citation statements)
references
References 58 publications
12
139
3
3
Order By: Relevance
“…jneurosci.org as supplemental material). Whereas previous studies have demonstrated such plasticity in the human cerebellum for motor learning (Imamizu et al, 2000(Imamizu et al, , 2003Ramnani et al, 2000;Ramnani and Passingham, 2001;Ungerleider et al, 2002;van Mier et al, 2004;Miall and Jenkinson, 2005;Penhune and Doyon, 2005;Puttemans et al, 2005), for the first time our study demonstrates plastic changes in cerebellar cortical parts of the "prefrontal loop" that occur as a direct consequence of manipulating the automaticity of rulebased information processing. Such activity reflects the acquisition of internal models of prefrontal information processing that contribute to the automatic execution of cognitive operations (Balsters and Ramnani, 2008).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…jneurosci.org as supplemental material). Whereas previous studies have demonstrated such plasticity in the human cerebellum for motor learning (Imamizu et al, 2000(Imamizu et al, , 2003Ramnani et al, 2000;Ramnani and Passingham, 2001;Ungerleider et al, 2002;van Mier et al, 2004;Miall and Jenkinson, 2005;Penhune and Doyon, 2005;Puttemans et al, 2005), for the first time our study demonstrates plastic changes in cerebellar cortical parts of the "prefrontal loop" that occur as a direct consequence of manipulating the automaticity of rulebased information processing. Such activity reflects the acquisition of internal models of prefrontal information processing that contribute to the automatic execution of cognitive operations (Balsters and Ramnani, 2008).…”
Section: Discussioncontrasting
confidence: 43%
“…These have been supported by empirical demonstrations of motor learning-related cerebellar plasticity using electrophysiology in nonhuman primates (Gilbert and Thach, 1977;Ojakangas and Ebner, 1992;Greger and Norris, 2005;Soetedjo and Fuchs, 2006;Medina and Lisberger, 2009) and numerous functional neuroimaging studies in humans (Friston et al, 1992;Imamizu et al, 2000Imamizu et al, , 2003Ramnani et al, 2000;Ramnani and Passingham, 2001;Ungerleider et al, 2002;van Mier et al, 2004;Miall and Jenkinson, 2005;Penhune and Doyon, 2005;Puttemans et al, 2005). Motor learning is likely to depend on information flow between cortical motor areas and cerebellar cortex via the pontine nuclei (Allen and Tsukahara, 1974;Wolpert and Kawato, 1998), and changes in the strength of synapses onto Purkinje cells (PCs; the principal computational units and output neurons of the cerebellar cortex).…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, our results suggest that this structure does not only reflect the consolidation of a newly learned sequence of movements (6,7,17,18), but that this physiological process is facilitated by sleep. Indeed, increases of activity within the striatum have previously been related to the acquisition of wrist movement sequences (19)(20)(21) per se, as well as the learning of MSL, as opposed to the mere increase in speed of finger movements (22). Moreover, such increase in striatal activity has also been seen following motor memory consolidation when sleep (10), or a 24-h delay including sleep is present after initial learning (23).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the repeated application of the mechanisms of dynamic stability seems to facilitate the adequate use of those mechanisms even in unfamiliar situations in order to regain balance. This improvement may be ascribed to a shift from prefrontal activity to a subcortical circuit, involving the cerebellum and basal ganglia, accompanied by increased automatic performance (Floyer-Lea and Matthews 2004;Puttemans et al 2005;Taube et al 2007). Several exercise interventions have so far shown to be effective in reducing the risk of falls in older adults by means of balance, coordination, or strength training (for review see Gillespie et al 2010).…”
Section: Discussionmentioning
confidence: 99%